Multidrug Resistant Klebsiella pneumoniae ST101 Clone Survival Chain From Inpatients to Hospital Effluent After Chlorine Treatment - Popa, Laura Ioana; Gheorghe, Irina; Barbu, Ilda Czobor; Surleac, Marius; Paraschiv, Simona; Măruţescu, Luminiţa; Popa, Marcela; Pîrcălăbioru, Graţiela Grădişteanu; Talapan, Daniela; Niţă, Mihai; Streinu-Cercel, Anca; Streinu-Cercel, Adrian; et al. (Frontiers in Microbiology, 2021)
In this paper we describe the transmission of a multi-drug resistant Klebsiella pneumoniae ST101 clone from hospital to wastewater and its persistence after chlorine treatment. Water samples from influents and effluents of the sewage tank of an infectious diseases hospital and clinical strains collected from the intra-hospital infections, during a period of 10 days prior to wastewater sampling were analyzed. Antibiotic resistant K. pneumoniae strains from wastewaters were recovered on selective media. Based on antibiotic susceptibility profiles and PCR analyses of antibiotic resistance genetic background, as well as whole-genome sequencing (Illumina MySeq) and subsequent bioinformatic analyses, 11 ST101 K. pneumoniae strains isolated from hospital wastewater influent, wastewater effluent and clinical sector were identified as clonally related. The SNP and core genome analyses pointed out that five strains were found to be closely related (with ≤18 SNPs and identical cgMLST profile). The strains belonging to this clone harbored multiple acquired antibiotic resistance genes (blaCTX-M-15, blaOXA-48, blaOXA-1, blaSHV-106, blaTEM-150, aac (3)-Iia, aac (6')-Ib-cr, oqxA10, oqxB17, fosA, catB3, dfrA14, tet(D)) and chromosomal mutations involved in antibiotic resistance (ΔmgrB, ΔompK35, amino acid substitutions in GyrA Ser83Tyr , Asp87Asn, ParC Ser80Tyr). Twenty-nine virulence genes involved in iron acquisition, biofilm and pili formation, adherence, and the type six secretion system - T6SS-III were identified. Our study proves the transmission of MDR K. pneumoniae from hospital to the hospital effluent and its persistence after the chlorine treatment, raising the risk of surface water contamination and further dissemination to different components of the trophic chain, including humans.